Formulasi Ekstrak Biji Kedelai (Glycine Max L.) Dalam Sediaan Gel Menggunakan Basis Hpmc:Uji Stabilitas Fisik Dan Efek Pada Kulit Manusia - Ulfa, Nisa Rachmania; , Anita Sukmawati, Ph.D., Apt (2016)
Soybean (Glycine max L.) is a popular plant in Indonesia, has a group of flavonoids active substances and is one of the food-producing natural antioxidants. Compounds that act as antioxidants are isoflavones. The purpose of this study is to determine the effect of different concentrations of HPMC to the physical stability of the gel including organoleptic, pH, viscosity, dispersive power, and adhesion during storage and determine the effect of different concentrations of HPMC on the effects of soy extract gel skin protection from the sun. Soybean extract was made into powder by freeze dry method, and then formulated into HPMC gelling base. Gels were made using HPMC 5%, 10%, and 20% containing 1 gram extract in 100 grams gel in each formula. The results show that increased concentration of HPMC can increase the viscosity and adhesive power, and decrease dispersive power, but the increase in concentration of HPMC did not affecting the pH. Test result showed the effect of gel soybean extract may serve as a protective for the skin from the sun, but the differences concentration of HPMC did not distinction effect skin protection from the sun.